Supply and demand relationships in the Malaysian cocoa market - Idris, Nurjihan (2013)
The Malaysian cocoa sector has undergone a structural transformation during the last few decades. Cocoa area and production have shown an increasing trend in the 1970s until 1990s. However, after 1990s and beyond, the cocoa land area and production declined significantly due to the following factors. They were; declining world prices, higher labour costs, loss of production due to pests and diseases along with a switch in the relative profitable crops such as oil palm have caused the decrease in cocoa production. Meanwhile, the domestic demand for grindings and import have expanded significantly. In view of the significant structural shift that took place in the industry, it is important to examine which of these factors are truly significant in explaining the cocoa market in Malaysia and to foresee the future of the Malaysian cocoa market in the short-run and long-run. Thus, the objectives of this thesis are; (i) to assess the relationship and examine the variables which influence the supply and demand of the Malaysian cocoa industry;and (ii) to forecast the supply and demand of the Malaysian cocoa industry. The models have been estimated using Autoregressive Distributive Lag (ARDL). The coefficients obtained are then used to carry out ex ante and ex post forecasts. The findings of this study imply that the producer prices of palm oil and government expenditure are the most sequential factors affecting the cocoa planted area in Malaysia. The fertilizer prices proved to have a significant effect on yield. The domestic as well as the import demand for cocoa are significantly affected by the Malaysian Index of Industrial Production, which implies that the increase in income of the importing nations leads to an increase in the grinding industry. Finally, the ex ante forecasts of cocoa supply and demand show that the supply and export of cocoa are increasing while the import and domestic demand are decreasing. The factors contributing to the increase in supply are; the high cocoa price and the increase in technology. Meanwhile, decrease in domestic demand is attributed to the low Index of Industrial Production. The ex post forecasts suggest opposite results. The supply and domestic demand of cocoa are exhibiting decreasing trend, while export and import are increasing. The contributing factors for the decrease in supply are; high prices of palm oil as competing crops and increase in fertilizer price. Meanwhile, the increase in export and import are attributed to the higher world GDP and Malaysian Industrial Index of Production which implies a growing demand from the grinding industry.